Libya -- Managing Public Investment After the Revolution : Background, Activities, Results and Proposals - Schiavo-Campo, Salvatore (World Bank, Washington, DC, 2016)
This report is intended to provide in one single document the background, principal recent and current World Bank activities and the proposed program of technical assistance to the Government in the area of public investment programming and management in post-revolution Libya. Aside from the convenience, both for the Bank and other international partners, of a synthesis of all major assessments and advice provided by the Bank in this central area of public sector management, this report shows the substantial continuity of diagnosis and assistance from the immediate aftermath of the Revolution through mid-2014. The first section recounts the early activities and, against that background, the second section summarizes the activities conducted and initial results achieved during FY2014. The concluding section lists the preliminary agreements with the Government on how to build on those initial results with complementary activities and deepening of a number of initiatives, specifically during FY2015 and with general indications for the subsequent years. The text of the report is limited to a summary of key issues and recommendations, with full details provided in the several annexes.